Two Strains of Covid-19 Model with Vaccination and the Effect of Awareness Program on Its Control - Anate A. O.; Adamu M. M.; Adamu M.S.; Kwami A. M. (Asian Journal of Science, Technology, Engineering, and Art, 2026)
The Covid-19 outbreak and the subsequent emergence of different viral strains posed a serious global public health challenge. This study proposes a mathematical model to analyze the transmission dynamics of two different Covid-19 strains and examine the effect of awareness on disease control. The study established the basic mathematical properties of the model, analyzed the disease-free and disease-endemic equilibria for both strains, conducted stability analysis, and computed the basic reproduction number, defined as R₀ = max(R₁, R₂). Stability conditions were examined for the strain-specific reproduction numbers, including cases in which R₁ < 1 while R₂ > 1 and R₂ < 1 while R₁ > 1. Numerical simulations were also conducted to support the analytical results and further illustrate the model dynamics. The findings show that increased awareness enhances vaccination uptake and reduces the basic reproduction number, thereby contributing to the control of disease transmission. The study concludes that awareness-based interventions play an important role in controlling the spread of Covid-19 strains through improved vaccination behavior and reduced transmission potential. These findings contribute to mathematical epidemiology by demonstrating the relevance of awareness-driven vaccination strategies in multi-strain infectious disease models and provide practical implications for public health authorities in strengthening awareness campaigns through media and social gatherings.